(untitled) (Jurnal Teknologi (Sciences & Engineering), 2019)
A comprehensive review using natural rubber in the modification of bitumen used for road construction is presented in this paper. The sources, types and properties of natural rubber are discussed briefly. The methods used by researchers to add natural rubber as a modifier for bitumen are also discussed. A literature review of the effects of natural rubber on the physical, mechanical and rheological properties of bitumen and the performance of asphalt mixtures over the past three decades is presented along with the cost analysis of using natural rubber as a modifier in comparison to using other polymers. Researchers in the field of the highway and pavement engineering need to find a method to deal with the most common pavement distress by using local additives such as natural rubber. It is expected that a special, cost effective and long lasting natural rubber modified flexible for road pavements, which is also fatigue and rut resistant, will be developed in the near future. This will reduce the amount of expenses required for the annual maintenance of asphalt mixtures around the world.